(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This Imam Abu Hanifa is a Muslim in the article of the world famous jurisprudence from scientists one as well as mind and wisdom symbol as east in literature separately attention taken. This in the article, Imam Azam image east in literature where in a way lighting analysis In particular, the article exactly this character motive comparative analysis presented will that is, Imam Azam image other in the nations where in a way formed and cultures between the differences open gives.